Topographic Evaluation of Apex and Root Canal of Maxillary Premolars in an Iranian Population - Naseri, Mandana; Momayez, Mojgan; Ahangari, Zohreh (Journal of Dental School, 2020)
Objective: Knowledge about the internal anatomy of the root canal and apical foramen is a critical prerequisite for root canal therapy and is necessary for the success of endodontic treatment. This study aimed to determine the distance of apical foramen from the anatomical apex and apical constriction, evaluate the deviation of apical foramen from the anatomical apex and specify the most common canal types in maxillary premolar teeth using stereomicroscope. Methods: In this laboratory experimental study, 100 extracted first and second maxillary premolars of patients presenting to dental clinics in Tehran were selected. After the disinfection of roots and access cavity preparation, apical foramen deviation and its distance from the anatomical apex were determined by introducing a #10 hand file into the canal and observation under stereomicroscope; 2% methylene blue was then injected into the canals and demineralization and clearing process were carried out to measure the distance of apical foramen from the apical constriction and evaluate the canal type. Results: The mean distance of apical foramen from the anatomical apex and apical constriction was 0.4-0.5 and 0.5-0.7 mm, respectively in maxillary first premolars and 0.3-0.7 and 0.6-1 mm, respectively in maxillary second premolars. In less than 17% of first premolars and 37% of second premolars, the canal followed a straight path to the anatomical apex without any deviation towards the mesiodistal or buccolingual directions. The most common canal type according to Vertucci’s classification was type IV in the first and type I in the second premolars. In general, 94% (n=47) of the first premolars and 46% (n=23) of the second premolars had 2 canals while the remaining teeth had a single canal. Conclusion: This study showed that the apical foramen in premolar teeth is located at a 0.3-0.7 mm distance from the anatomical apex and 0.5-1 mm distance from the apical constriction. In more than 83% of first premolars and 63% of second premolars the apical foramen did not correspond to the anatomical apex. First and second premolars had 2 canals in 94% and 46% of cases, respectively.